Presence of a limited number of essential nucleotides in the promoter region of mouse ribosomal RNA gene. - Kishimoto, T (1985)
Point mutations are introduced into a mouse rDNA fragment containing the promoter region by a sodium bisulfite method and the mutants are tested for the ability of accurate transcription initiation in vitro. The results indicate that the change, G to A, at -7 completely eliminates the promoter activity, and those at -16 and at -25 decrease it to about 10% and 50%, respectively. On the other hand, the substitutions at +9, +4, -2, -9 and -39 do not alter the template activity significantly. It is concluded that there are limited but distinct nucleotides that are essential for the transcription initiation of this gene. This sort of absolute requirement for single specific bases is not reported in protein coding genes transcribed by RNA polymerase II. We propose that these rigid recognition signals which we have found are the molecular basis for the strong species-dependency of the transcription machinery of RNA polymerase I system. A model is presented in which a transcription factor interacts with the rDNA promoter from one side of the DNA double-helix with essential contacts at these bases.